(untitled) (International Journal of Scientific Trends, 2024)
The investment climate plays a significant role in solving the problems of ensuring sustainable development of countries, regions, municipalities, and organizations. Its most important component is investment attractiveness, which is influenced by many factors, geographical location, availability of natural, material and technical, human resources, production structure, production and social infrastructure, etc. The economic category "investment attractiveness" is constantly in the field of view of researchers, as it determines innovative activity, economic growth, standard of living and quality of life of the population.